Chemotactic factor-induced polarization, receptor redistribution, and locomotion of human blood monocytes. - Islam, L N (1988)
The locomotor response of human blood monocytes to chemotactic factors was studied using a polarization assay on cells in suspension and by filming locomotion on albumin-coated glass. Cells in optimal (5 x 10(-9) M) but uniform concentrations of N-formyl-methionyl-leucyl-phenylalanine (FMLP) polarized well and showed a 'persistent random walk' type of locomotion, whereas in supraoptimal concentrations (10(-7) M), the cells took erratic paths and polarized poorly, suggesting that monocytes cannot develop an anteroposterior polarity if hit by ligand molecules at many points on the cell surface simultaneously. Monocyte polarization in chemotactic factors at 37 degrees was transient and was gradually lost after 15-20 min. Likewise, the ability to form Fc rosettes after this time was gradually lost, suggesting loss of functional receptors from the cell surface with time. In optimally polarized cells, Fc rosettes were frequently localized at the head of the cell. This localization also was lost with time. Using pure chemotactic factors (FMLP, C5a, leukotriene B4) we found, as reported earlier (Cianciolo & Snyderman 1981), that polarization was restricted to a subpopulation (approximately 60% of cells) that responded to multiple attractants. However, 80-90% of monocytes polarized in response to combinations of any of the above pure attractants with candida-activated serum. This suggests that the subpopulation that lacks receptors for classical chemotactic factors nevertheless has locomotor capacity and can respond to undefined factors in activated serum, and that the great majority of blood monocytes is motile if appropriately stimulated.